Hypoxia-inducible factor 1α protects peripheral sensory neurons from diabetic peripheral neuropathy by suppressing accumulation of reactive oxygen species - Rangel Rojas, Daniel; Kuner, Rohini; Agarwal, Nitin (Journal of molecular medicine, 2018)
Diabetic peripheral neuropathy (DPN) is one of the most common diabetic complications. Mechanisms underlying nerve damage and sensory loss following metabolic dysfunction remain largely unclear. Recently, hyperglycemia-induced mitochondrial dysfunction and the generation of reactive oxygen species (ROS) have gained attention as possible mechanisms of organ damage in diabetes. Hypoxia-inducible factor 1 (HIF1α) is a key transcription factor activated by hypoxia, hyperglycemia, nitric oxide as well as ROS, suggesting a fundamental role in DPN susceptibility. We analyzed regulation of HIF1α in response to prolonged hyperglycemia. Genetically modified mutant mice, which conditionally lack HIF1α in peripheral sensory neurons (SNS-HIF1α−/−), were analyzed longitudinally up to 6 months in the streptozotocin (STZ) model of type1 diabetes. Behavioral measurements of sensitivity to thermal and mechanical stimuli, quantitative morphological analyses of intraepidermal nerve fiber density, measurements of ROS, ROS-induced cyclic GMP-dependent protein kinase 1α (PKG1α), and levels of vascular endothelial growth factor (VEGF) in sensory neurons in vivo were undertaken over several months post-STZ injections to delineate the role of HIF1α in DPN. Longitudinal behavioral and morphological analyses at 5, 13, and 24 weeks post-STZ treatment revealed that SNS-HIF1α−/− developed stronger hyperglycemia-evoked losses of peripheral nociceptive sensory axons associated with stronger losses of mechano- and heat sensation with a faster onset than HIF1αfl/fl mice. Mechanistically, these histomorphologic, behavioral, and biochemical differences were associated with a significantly higher level of STZ-induced production of ROS and ROS-induced PKG1α dimerization in sensory neurons of SNS-HIF1α−/− mice as compared with HIF1αfl/fl. We found that prolonged hyperglycemia induced VEGF expression in the sciatic nerve which is impaired in SNS-HIF1α mice. Our results indicate that HIF1α is as an upstream modulator of ROS in peripheral sensory neurons and exerts a protective function in suppressing hyperglycemia-induced nerve damage by limiting ROS levels and by inducing expression of VEGF which may promote peripheral nerve survival. Our data suggested that HIF1α stabilization may be thus a new strategy target for limiting sensory loss, a debilitating late complication of diabetes.Key messages• Impaired hypoxia-inducible factor 1α (HIF1α) signaling leads to early onset of STZ-induced loss of sensation in mice.• STZ-induced loss of sensation in HIF1α mutant mice is associated with loss of sensory nerve fiber in skin.• Activation of HIF1α signaling in diabetic mice protects the sensory neurons by limiting ROS formation generated due to mitochondrial dysfunction and by inducing VEGF expression.
Gesehen am 10.04.2019